2015
DOI: 10.1016/j.cgh.2015.04.184
|View full text |Cite
|
Sign up to set email alerts
|

Relamorelin Relieves Constipation and Accelerates Colonic Transit in a Phase 2, Placebo-Controlled, Randomized Trial

Abstract: Relamorelin acts in the colon to significantly reduce symptoms of constipation and accelerate CT in patients with chronic constipation, compared with placebo. ClinicalTrial.Gov registration number: NCT01781104.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 27 publications
(37 reference statements)
2
29
0
1
Order By: Relevance
“…This finding of mild diarrhea is not surprising, given prior observations of the presence of ghrelin receptors in the enteric neural control of the colon, 39 as well as the relief of constipation and acceleration of colonic transit with relamorelin in patients with chronic constipation. 40 …”
Section: Discussionmentioning
confidence: 99%
“…This finding of mild diarrhea is not surprising, given prior observations of the presence of ghrelin receptors in the enteric neural control of the colon, 39 as well as the relief of constipation and acceleration of colonic transit with relamorelin in patients with chronic constipation. 40 …”
Section: Discussionmentioning
confidence: 99%
“…The required sample size was estimated via prospective power analysis. The sample size was calculated based on previous published studies on enterokinetic agents that improved the CTT . Based on previous data, we hypothesized that DA‐9701, when used to treat patients with constipation, would decrease the CTT compared with before treatment .…”
Section: Methodsmentioning
confidence: 99%
“…The safety and efficacy of relamorelin on chronic constipation have also been evaluated. In a Phase II clinical trial, relamorelin significantly reduced the symptoms of constipation and accelerated colonic transit in female patients with chronic constipation . Furthermore, the same study showed that relamorelin rapidly increased colonic contractions without any change in background irregular contractions .…”
Section: Results Of Major Clinical Trials and Current Statusmentioning
confidence: 86%